Michonneau, Stéphane: Fue ayer, Belchite. Un pueblo frente a la cuestión del pasado, Zaragoza, Prensas de la Universidad de Zaragoza, 2017, 486 páginas - Pérez-Olivares, Alejandro (Hispania Nova, 2018)
--